Ureteroscopy:The First-Line Treatment for Distally Located Ureteral Stones Smaller Than 10 mm - Kiraç, Mustafa; Atkin, Mehmet Sinan; Deniz, Nuri; Biri, Hasan (Urology Journal, 2014)
Purpose: To compare the efficacy of different treatment strategies for distal ureteral stones smaller than 10 mm. Material and Methods: A total 127 patient were included in the study. Based on the treatment modality , patients were divided into three groups. Patients in group 1 only received conventional treatment including daily hydration of 2500 mL, ciprofloxacin, diclofenac sodium and a spasmolytic agent; group 2 patients received conventional treatment (daily hydration of 2500 mL, ciprofloxacin, diclofenac sodium and a spasmolytic agent) and tamsulosin 0.4 mg orally daily for 4 weeks; and group 3 patients underwent ureteroscopy. Patients were further subdivided into 2 categories based on maximum stone diameter: category A (less than 5 mm) and category B (5.0-9.9 mm). Following treatment, all groups were compared in terms of stone-free rate and time to expulsion. Results: Following treatment, the stone-free rates for groups 1, 2 and 3 were 48.7%, 59.5% and 95.6%, respectively (P < .0001). The mean expulsion times for groups 1, 2 and 3 were 15.3 ± 5.33, 15.1 ± 5.5 and 1.95 ± 2.2 days, respectively (P < .001). Compared to the other treatments, the stone-free rate and mean expulsion time in the ureteroscopy group were significantly increased and decreased, respectively. Conclusion: There are several treatment options for distal ureteral stones. Based on our data,we conclude that ureterorenoscopy should be the standard of care for distal ureteral stones smaller than 10 mm.